ANALISIS LINGKUNGAN INTERNAL DAN EKSTERNAL PADA USAHA KEDAI KOPI KADAKA CAFETARIA MENGGUNAKAN QSPM - Nadya Hasna Latifa; Dini Rochdiani (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Coffee plants are plantations that have existed for a long time ago to be cultivated plants. Today, coffee drinks are no longer just for consumption but can be complementary to daily activities. The amount of coffee consumption is expected to continue to increase along with the increasing income of the middle class, making coffee shop businesspeople sure to run their businesses. KADAKA Cafetaria is one of the new coffee shops that have problems with its sales. Also, there are similar competitors in the vicinity. Thus, it is necessary to know the alternative marketing strategies that can be used by KADAKA Cafetaria coffee shops so they can face competition. The design in this study uses qualitative design and case study research techniques. The analysis tool used is using the IFE, EFE, IE, SWOT, then QSP matrices. The results of the IE matrix show that the company is in a position to grow and develop. Four alternative strategies are formulated from the results of the SWOT and QSP matrices with the priority strategy is to increase promotional activities.